THE RELATIONSHIP OF NATURE AND CULTURE: NATURE AS A CULTURAL VALUE (American Journal of Interdisciplinary Research and Development, 2025)
The article discusses the basic concepts of environmental education, the importance of environmental protection, reveals modern methods of developing environmental consciousness, including environmental education, education, culture and also educational activities.